2021
DOI: 10.4103/jfmpc.jfmpc_14_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and mortality in COVID-19 SARI versus non COVID-19 SARI cases from Western Rajasthan, India

Abstract: Background: In March 2020, the Indian Council of Medical Research (ICMR) issued guidelines that all patients presenting with severe acute respiratory infections (SARI) should be investigated for coronavirus disease 2019 (COVID-19). Following the same protocol, in our institute, all patients with SARI were transferred to the COVID-19 suspect intensive care unit (ICU) and investigated for COVID-19. Methods: This study was planned to examine the demographical, clinical fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Notably, over one-third of observed SARI deaths were linked to SARS-CoV-2 detection, underscoring the substantial mortality risk posed by the virus among SARI patients. This trend parallels findings from an Indian study involving 500 hospitalized SARI patients, indicating a higher mortality rate in COVID-19-positive SARI cases (34.1%) compared to COVID-negative instances (20.1%) [ 19 ]. Other studies also demonstrated that SARI patients had three times more risk of death due to COVID-19 during the pandemic than other respiratory viruses [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, over one-third of observed SARI deaths were linked to SARS-CoV-2 detection, underscoring the substantial mortality risk posed by the virus among SARI patients. This trend parallels findings from an Indian study involving 500 hospitalized SARI patients, indicating a higher mortality rate in COVID-19-positive SARI cases (34.1%) compared to COVID-negative instances (20.1%) [ 19 ]. Other studies also demonstrated that SARI patients had three times more risk of death due to COVID-19 during the pandemic than other respiratory viruses [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…The pandemic revealed that SARI mortality was no longer solely attributed to influenza, but also heavily impacted by COVID-19. Countries like Brazil and India experienced a dramatic rise in SARI cases and deaths during the pandemic period [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical presentation was similar in both groups (Pannu et al, 2021 ). Another study conducted in India (Sharma et al, 2021 ) enrolled 500 participants, in which only 88 were positive for COVID-19. Similar to the study conducted in North India, the authors observed a similar clinical profile between individuals with COVID-19 and SARI, and also, older patients were diagnosed with COVID-19 (Sharma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in India (Sharma et al, 2021 ) enrolled 500 participants, in which only 88 were positive for COVID-19. Similar to the study conducted in North India, the authors observed a similar clinical profile between individuals with COVID-19 and SARI, and also, older patients were diagnosed with COVID-19 (Sharma et al, 2021 ). Finally, the most extensive study in India accounted for nearly 5,000 individuals with SARI, out of which 104 were diagnosed with COVID-19 (Gupta, N. et al, 2020 ), being the COVID-19 group had an increased number of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study analysing 500 patients hospitalized due to SARI in India showed a higher mortality rate among cases associated with COVID-19 (34.1%) compared with those not associated with COVID-19 (20.6%). 17 …”
Section: Discussionmentioning
confidence: 99%